Investor Reactions on Emitents Who Published Corporate Sukuk Listed in Indonesia Stock Exchange - Kasman Damang; Eka Afnan Troena; Muhammad Ali; Abdul Hamid Habbe (Magister Management, Hasanuddin University, 2020)
This study applied an event study approach (event study). The event tested the announcement of Sukuk emissions and market reactions as indicated by the existence of a significant Abnormal Return on the date of Sukuk emissions and it changed within the activity of Stock Trader of the Corporation Sukuk Issuer. Observation period between 2009-2018, there was 129 Sukuk emissions in Indonesia Stock Exchange. The number of samples taken was 26 emissions of Sukuk which make emissions from 12 issuers that met the set criteria. Data were analyzed using descriptive statistical analysis, independent t-test, t-paired test, and regression analysis. Furthermore, the data were processed using IBM SPSS for Windows Software. The results showed that there was a difference in Average Abnormal Return (AAR) before and after the announcement of Sukuk emissions. However, the average value of the difference was not statistically significant. There was a positive market reaction on Average Abnormal Return (AAR) before the announcement of Sukuk emissions. There was a positive market reaction on Average Abnormal Return (AAR) after the announcement of Sukuk emissions. There were differences in the Average Trading Volume Activity (ATVA) before and after the announcement of Sukuk emissions. However, the average value of the difference was not statistically significant. There was a significant market reaction on Average Trading Volume Activity (ATVA) before the announcement of Sukuk emissions. There was a significant market reaction of Average Trading Volume Activity (ATVA) after the announcement of Sukuk emissions. Furthermore, this study also found that Sukuk to Equity Ratio (SER) had a positive effect, but not significantly on the level of Return on Assets (ROA), Return on Equity (ROE), and Earning per Share (EPS), but it was not significant. These insignificant effects of SER on the issuer's ROA, ROE and EPS were caused by the relatively small proportion of Sukuk value compared to the value of assets and company equity.